2008
DOI: 10.1097/wnp.0b013e31818f4fec
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Connection of Motor Areas in Humans

Abstract: We attempted to clarify functional interhemispheric connections of motor cortex (MC) by investigating cortico-cortical evoked potentials from human brains in vivo. Three patients with intractable epilepsy who underwent invasive EEG monitoring with subdural electrodes as presurgical evaluation were studied. Electric pulse stimuli were delivered in a bipolar fashion to two adjacent electrodes on and around MC. Cortico-cortical evoked potentials were recorded by averaging electrocorticograms from the contralatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
(38 reference statements)
2
21
1
Order By: Relevance
“…Consistent with our previous report [Terada et al, 2008], CCEP responses were recorded from the contralateral hemisphere in the current study. Compared with the previous study, this study investigated a larger number of patients, and furthermore succeeded to stimulate not only f-MA but also nf-MA and SA.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Consistent with our previous report [Terada et al, 2008], CCEP responses were recorded from the contralateral hemisphere in the current study. Compared with the previous study, this study investigated a larger number of patients, and furthermore succeeded to stimulate not only f-MA but also nf-MA and SA.…”
Section: Discussionmentioning
confidence: 73%
“…Previously, we recorded CCEP responses from the contralateral hemisphere by stimulating facial motor area (f-MA) in three epilepsy patients [Terada et al, 2008]. Our result demonstrated that most of these interhemispheric CCEP responses showed initial positive triphasic waveforms (P1-N1-P2).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations